Feminism in Shashi Deshpande's Novels: An Exploration of Women's Struggles and Expression in Shashi Deshpande's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The purpose of the research is to see if Shashi Deshpande's ladies really express themselves orwhether they eventually give in to endurance. All of her books have been taken into account for thisstudy's purposes, although the focus of this research is on three of her main works The Dark Holds NoTerrors, Roots and Shadows, and That Long Silence. These three books have received honors and havebeen published in many different languages. The goal of this essay is to examine Shashi Deshpande'sportrayal of women characters in her books in order to comprehend and respect their struggles as aresult of the competing influences of modernity and tradition. It evaluates how they react to newsituations in life critically in order to make them fit within modern society. The research takes intoaccount the issues that her characters face without delving too far into the novelist's belief in theperfect solution for various types of difficulties. which have faced the aforementioned challenges